Mind your words: Oncologists' communication that potentially harms patients with advanced cancer: A survey on patient perspectives. Issue 5 (11th November 2021) - Westendorp, Janine; Evers, Andrea W. M.; Stouthard, Jacqueline M. L.; Budding, Janneke; van der Wall, Elsken; Plum, Nicole M. F.; Velting, Mirjam; Francke, Anneke L.; van Dulmen, Sandra; olde Hartman, Tim C.; Van Vliet, Liesbeth M.
Abstract : Background: Many complaints in medicine and in advanced illnesses are about communication. Little is known about which specific communications harm. This study explored the perspectives of patients with advanced cancer about potentially harmful communication behaviors by oncologists and helpful alternatives. Methods: An online survey design was used that was based on literature scoping and patient/clinician/researcher input. Patients with advanced cancer (n = 74) reflected on the potential harmfulness of 19 communication situations. They were asked whether they perceived the situation as one in which communication could be harmful (yes/no). If they answered "yes, " they were asked whether they perceived the examples as harmful (yes/no) or helpful (yes/no) and to provide open comments. Results were analyzed quantitatively and qualitatively (content analysis). Results: Communication regarding information provision, prognosis discussion, decision‐making, and empathy could be unnecessarily potentially harmful, and this occurred in various ways, such as making vague promises instead of concrete ones (92%), being too directive in decision‐making (qualitative), and not listening to the patient (88%). Not all patients considered other situations potentially harmful (eg, introducing the option of refraining from anticancer therapy [49%] and giving too much [prognostic] information [60%]). Exploring each individual patients' needs/preferences seemed to be a precondition for helpful communication. Conclusions: This article provides patient perspectives on oncologists' unnecessarily potentially harmful communication behaviors and offers practical tools to improve communication in advanced cancer care. Both preventable pitfalls and delicate challenges requiring an individualized approach, where exploration might help, are described. Although providing difficult and unwelcome news is a core task for clinicians, this study might help them to do so while preventing potentially unnecessary harm. Abstract : Communication may be potentially harmful in relation to 1) information provision, 2) prognosis discussion, 3) decision‐making, or 4) empathy. This article describes both preventable pitfalls (eg, patient vs Ms X ) and delicate challenges (eg, introducing the option of no anticancer therapy) where exploring patients' needs and preferences may help.